Aluminium Composites Fabrication Technique and Effect of Improvement in Their Mechanical Properties – A Review. (2018) - Ravikumar, M; Reddappa, H.N; Suresh, R.
Abstract: Aluminium metal matrix composites are extensively used in automobile industries and aerospace. Aluminium metal matrix composites (AMMCs) reinforced by firm ceramic particulates which provide expressively improved mechanical properties by the addition of ceramics particles into the matrix. The ceramic particles dissolve into aluminium matrix, which helps to produce a high bonding strength among the particles and matrix materials. The adding of reinforcement particles into the AMMCs increases the specific strength, stiffness, wear rate, fatigue and creep properties when it is compared with conventional engineering resources. The main aim of this paper is to review the benefits of using MMCs over other Al/Al alloy with respect to mechanical properties. It is possible to optimize the wt. % of reinforcement in to metal matrix by using the proper proportion and combination of different particle as reinforcement